Protein First: Whey Protein Administration Strategy in Critically ill Patients - Suharsoyo, Tomy; Prasamya, Erlangga (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2026)
Background: Critically ill patients in the intensive care unit (ICU) frequently develop hypercatabolic states associated with progressive muscle wasting and immune dysfunction. Meeting adequate protein targets remains a persistent challenge in standard ICU nutrition practice.Methods: A narrative review of the literature was conducted by searching PubMed, MEDLINE, and Google Scholar using the keywords “whey protein,” “critically ill,” “ICU nutrition,” “protein-first strategy,” “enteral nutrition,” and related terms. Articles published between 2015 and 2025 were prioritized, and foundational earlier studies were included where relevant. Randomized controlled trials, systematic reviews, meta-analyses, observational studies, consensus guidelines, and mechanistic studies were included. Articles without full-text availability or not relevant to critical care nutrition were excluded.Results: Whey protein is biologically characterized by rapid absorption, a rich essential amino acid profile, and a high leucine content that may activate the mTORC1 pathway to stimulate muscle protein synthesis. Whey protein–based enteral formulas have been shown in selected studies to facilitate achievement of recommended protein targets (1.2–2.5 g/kg/day) with acceptable gastrointestinal tolerance. Some evidence suggests potential benefits in nitrogen balance and inflammatory markers; however, evidence for consistent improvement in hard clinical outcomes—including mortality, ventilator duration, and ICU length of stay—across the general critically ill population remains limited. Most supportive studies are small, single-center, or focused on specific subpopulations, and several are feasibility assessments rather than outcome trials.Conclusion: Whey protein is a biologically plausible and practically useful component of individualized ICU nutrition. A “Protein First” approach using whey-based formulas may assist in meeting recommended protein targets; however, current evidence does not support claims of universal outcome benefit. Individualized dosing—with particular caution in patients with renal or hepatic impairment—remains essential.